Incidence of urinary retention in a tertiary post operative hospital - De Menezes Silveira, Gylmara Bezerra; Batista, Hermes Melo Teixeira; De Menezes Silveira, Gylsara Bezerra; Bezerra, Italla Maria Pinheiro; Valenti, Vitor Engracia [UNESP]; De Abreu, Luiz Carlos (Springer Nature, 2015)
Patients in the immediate post-operative period have several clinical features and when they are admitted in the post-anesthetic recovery room the signs and symptoms that affect the patient physically and psychologically resulting of surgical procedures begin to emerge. Urinary retention occurs frequently in these patients, as some anesthetics contribute to the development of this clinical condition. This research aims to analyze the incidence of urinary retention after surgery of patients of various specialties, correlating the type of anesthesia and the need for urinary catheterization. This study is characterized as exploratory, descriptive, with quantitative approach and was performed in a hospital of high complexity in Juazeiro do Norte. The sample was composed of the patients admitted to the post-anesthetic recovery room and during that time they presented urinary retention. Data analysis was demonstrated by the tables relating to the literature. The study contributed to the growth of scientific knowledge for hospital staff under study, as there were a large number of species records about urinary retention of patients undergoing surgical procedures that were admitted to the patient unit, especially in surgical units. That worried the nursing staff on the efficiency of systematization so there was an improvement in the quality of care, as many times, such deductions were accompanied by distension and suprapubic pain. Through these results, we could identify some interventions that have contributed to solve this nursing diagnosis, involving the whole multidisciplinary team and ensure the patient unit staff understood holistically the issues involved in this clinical condition and to be more involved in this process.
Keywords: Impact; Nursing; Urinary retention